LARP Politics and Hyperreality - Sutherland, Paul (Do Not Research, 2024)
Describing political agitation as LARP suggests a more complicated relationship between images and reality than to simply decry these political agitations as naïve and disconnected – indicating a deeper and more considered set of logics and motivations. I argue that the complicated relationship between images and reality suggested by the phrase ‘LARP comes after farce’ can be understood by examining it according to Baudrillard’s notion of simulation and hyperreality.